A retrospective cross-sectional study on the association between tobacco smoking and incidence of ST-segment elevation myocardial infarction and cardiovascular risk factors. Issue 1079 (11th August 2015) - Steele, Lloyd; Lloyd, Amelia; Fotheringham, James; Sultan, Ayyaz; Iqbal, Javaid; Grech, Ever D
ABSTRACT: Background: Cigarette smoking is a well-established risk factor for the development of coronary heart disease. However, the relationship between smoking and acute ST-segment elevation myocardial infarction (STEMI) is less well described. Objective: To determine the relative risk of acute STEMI in smokers and ex-smokers, compared with individuals who had never smoked. Methods: This observational study studied all patients with STEMI undergoing percutaneous coronary intervention (PCI) in South Yorkshire, UK from 1 January 2009 to 6 April 2012. Additional contemporary demographical data for the South Yorkshire population, supplied by the Office for National Statistics, allowed derivation of the incidence rate of STEMI in South Yorkshire—both overall and stratified by smoking status. Incidence rate ratios and population attributable risk (PAR) were calculated to quantify STEMI risk. Results: There were 1715 STEMIs in 1680 patients during the study period. Smoking status was obtained in 96.2% patients. The prevalence of smoking was 47.3% in patients with STEMI and 22.0% in the general population. In patients with STEMI, smokers were ∼10 years younger, mean (SD) 57.2 (11.1) years, than never-smokers, 66.4 (12.1) years, and ex-smokers, 67.9 (11.9) years. The age-standardised incident rate ratio of STEMI was 5.2 (4.5–6.1) for current smokers and 1.1 (1.0–1.3) for ex-smokers, with the reference group being never-smokers for both. Almost 50% of STEMIs were attributable to smoking (PAR=48.3%). Conclusion: Cigarette smoking is associated with a fivefold increased risk of STEMI. Smoking cessation reduced this risk to a level similar to never-smokers.